2018
DOI: 10.1103/physreva.97.032315
|View full text |Cite
|
Sign up to set email alerts
|

Squeezing-enhanced phase-shift-keyed binary communication in noisy channels

Abstract: We address binary phase-shift-keyed communication channels based on Gaussian states and prove that squeezing improves state discrimination at fixed energy of the channel, and also in the presence of phase diffusion. We then assess performances of homodyne detection against the ultimate quantum limits to discrimination and show that homodyning achieves optimality in the large-noise regime. Finally, we consider noise in the preparation of the seed signal (before phase encoding) and show that, also in this case, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Our results provide a clear departure from the case of phase-covariant Gaussian channels and prove the unconditional advantage of using non-classical Gaussian light in a physically motivated communication setting. We note that several works observed an enhancement in discrimination and communication in presence of phase noise via the addition of squeezing to coherent states, though with several restrictions on sources and measurements [23,[25][26][27][28][29]. To our knowledge, our work is the first to prove an unconditional advantage.…”
Section: Lossesmentioning
confidence: 66%
See 1 more Smart Citation
“…Our results provide a clear departure from the case of phase-covariant Gaussian channels and prove the unconditional advantage of using non-classical Gaussian light in a physically motivated communication setting. We note that several works observed an enhancement in discrimination and communication in presence of phase noise via the addition of squeezing to coherent states, though with several restrictions on sources and measurements [23,[25][26][27][28][29]. To our knowledge, our work is the first to prove an unconditional advantage.…”
Section: Lossesmentioning
confidence: 66%
“…This can happen when the relative phase drifts during transmission due to a physical mechanism in the medium, e.g., Kerr non-linearities and temperature fluctuations in optical fiber [12][13][14] or turbulence effects in free space [15]; but it can also be an effective result of other mechanisms, e.g., the use of a photodetector to measure the signals or the presence of a malicious eavesdropper [16,17]. Several works analyzed the effect of phase noise on common communication methods based on coherent states encodings [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal situation corresponds to squeezed coherent states with PSK encoding. This alphabet was studied in [ 18 , 23 ] and is further explored here. What is more, we have shown that this case is valid for more general values of the angular parameters and , provided .…”
Section: Discussionmentioning
confidence: 99%
“…Note that this optimality condition does not hold for a general squeezed state. This is equivalent to the squeezed states studied in [ 18 ], even though the authors had fixed from the start. This means that their expression is actually valid for more general values of and as we have shown here.…”
Section: Helstrom Bound For Squeezed Coherent Statesmentioning
confidence: 97%
See 1 more Smart Citation